WAYS TO IMPROVE THE EFFECTIVENESS OF FOREIGN LANGUAGE LEARNING IN HIGHER EDUCATION INSTITUTIONS USING COMMUNICATION TECHNOLOGIES - Ibragimova Feruza Holboyevna (International Journal of Literature and Language Studies, 2026)
Abstract. This article examines the effectiveness of communicative learning technologies as a means of developing communicative competence in foreign language learning among students at a pedagogical university. The purpose of this article is to analyze the effectiveness of communicative learning technologies in foreign language learning by university students.